Endovascular intervention vs. microsurgery on the prognosis of anterior circulation blood blister-like aneurysm: A cohort study - Tan, Haibin; Zhang, Tian; Huang, Guangfu; Li, Zhili; Wang, Zhenyu; Cheng, Meixong; Liu, Ling; Liu, Lingtong (Frontiers in Neurology, 2023)
Background: There are no universally acknowledged standardized treatment strategies for blood blister-like aneurysms (BBAs). This study compared the prognosis of patients with BBA who underwent craniotomy microsurgery vs. endovascular intervention. Methods: This retrospective cohort study included patients with BBA treated between September 2009 and August 2020 at Sichuan Provincial People’s Hospital affiliated to the Sichuan Academy of Medical Science. Patients were divided into the microsurgery and endovascular groups. The preoperative Hunt-Hess grade and modified Fisher grade were collected. The intraoperative and postoperative complications (including intraoperative aneurysm rupture and hemorrhage, postoperative cerebral hemorrhage, and BBA recurrence) were recorded. Results: Seventy-two patients were included: 28 and 44 in the microsurgery and endovascular groups, respectively. Only the preoperative Fisher grade was different between the two groups (P=0.041). The proportion of patients with good outcomes was lower in the microsurgery group (28.6%) than in the endovascular group (72.7%), and the mortality rate was higher in the microsurgery group (32.1%) than in the endovascular group (11.4%) (P<0.05). After adjustment for the modified Fisher grade, the multivariable analysis showed that compared with craniotomy microsurgery, an endovascular intervention was associated with the prognosis of patients with BBA (OR=0.128, 95%CI: 0.040-0.415, P<0.001). The rate of complications (intraoperative hemorrhage, cerebral infarction, and recurrence) was higher in the microsurgery group than in the endovascular group. Conclusion: In patients with BBA, an endovascular intervention appears to be associated with a better prognosis compared with craniotomy microsurgery.